INFLUENCE OF ZINCOVIT DROP (NUTRITIONAL FOOD SUPPLEMENT) ON IMMUNE SYSTEM IN NORMAL AND CYCLOPHOSPHAMIDE INTOXICATED WISTAR RATS - SATYAM, SHAKTA MANI; KURADY, LAXMINARAYANA BAIRY (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of the present study was to investigate the influence of Zincovit (ZVT) drop (nutritional food supplement) on the immune system in normal healthy and cyclophosphamide (CP) intoxicated Wistar rats. Methods: The study was carried out in healthy and immunotoxic Wistar rats (CP; 20 mg/kg/day) with ZVT drop (a combined formulation of multivitamin-multimineral, flaxseed oil, and lysine) at the dose of 25 and 50 mg/kg/day for 45 days. Hematological and immunological parameters, such as immunoglobulin (Ig)G, IgM, interferon-Î³, interleukin-2, and interleukin-4, were assessed. In addition, histopathological examination of the spleen was also performed. Results: There were no significant changes in all the hematological parameters such as total leukocyte, differential leukocyte, total erythrocyte, and total platelets count, hemoglobin amount and also the immunological parameters such as IgG, IgM, interferon-Î³, and interleukin-4 level among the treatment groups except interleukin-2. There was a significant increase in interleukin-2 level in the group of animals treated with ZVT drop at the dose of 25 mg/kg (p<0.001) and 50 mg/kg (p<0.05) in comparison with normal control animals. Conclusion: The present study revealed the immunomodulatory effect of ZVT drop at the dose of 25 and 50 mg/kg/day in normal healthy Wistar rats. Keywords: Zincovit drop, Flax seed oil, Multivitamin-multimineral nutritional food supplement, Cyclophosphamide, Immunomodulatory.